Proxy-driven free-form deformation by topology-adjustable control lattice - Zhang, Yuzhe (2021)
This paper presents a flexible free-form deformation (FFD) method that overcomes two limitations of many FFD methods: the cumbersome interface and the fixed topology of the control lattice. The novelty of the method mainly lies in two aspects: (1) a specifically-tailored T-spline volume with its local refinement is introduced to define the deformation space and construct the deformation tool, and (2) a proxy represented as a three-dimensional mesh close to the object to be deformed is constructed from the control lattice of the T-spline volume and is used to manipulate and drive the deformation. While the method inherits all the virtues of FFD such as C2 continuous local and global modifications, the proxy provides a much concise and intuitive interface for the user to edit the deformation in a way similar to cage-based deformations. Moreover, the method allows local topology changes of the proxy after parameterization, which is not available for most FFD methods or even cage-based deformations. These features enable more complicated free-form deformation to be achieved in a flexible and intuitive manner, as demonstrated by many experimental examples.